Synthesis Of Titanium Dioxide Thin Film For Photocatalytic Activity Via Green Sol-Gel Route - Abd Yazid, Nurul Shuhadah (2020)
TiO2 thin film coating has been a scope of interest for the purpose of photocatalytic application due to its superior photocatalyst properties. Nowadays, complex formulation or various techniques are deployed due to the drawbacks of TiO2 itself which has large band gap and low efficiency towards visible region. Thus, in this research, the main objective is to produce TiO2 thin film photocatalyst coating via sol-gel dip coating method using green sol-gel formulation (without solvent). First objective is to investigate the influences of solvent with ethanol (E16 and E8) and without ethanol (E0) at five and ten dipping numbers and heat treatment (500°C and 600°C) on the characteristic of the deposited TiO2 thin film. The main characteristics such as crystalline phases, crystallites size, phase composition, and surface morphology of the deposited thin films are reported. Second objective is to synthesis the hydrolysis ratio, r (16, 10, 8, and 5) between deionized water and TTiP precursor on the deposited TiO2 thin film especially its photocatalytic characteristics particularly focusing on the green sol-gel route. Third objective is to evaluate the photocatalytic performance of the deposited TiO2 thin film via green sol-gel route under UV-light and visible light using photo degradation method of methylene blue.TiO2 thin film characteristic such as its crystalline phases were analysed using XRD and RAMAN, while the crystallites size and phases composition were calculated using Scherrer’s equation and Spurr’s equation respectively. The surface morphologies and films thicknesses were analysed using SEM. The band gap value was obtained from UV-vis spectrum and Tauc plot equation. The photocatalytic test was conducted using color degradation method of methylene blue exposed under irradiation of UV-light and visible light for five hours. It is found that TiO2 thin film fabricated via novel green sol gel route with the hydrolysis ratio, r=5 (R32:6) showed the best photocatalytic characteristic and performance which possess an important characteristic of without ethanol (E0), mixed crystalline phases of anatase and rutile and consume low heat treatment temperature of 500°C. The crystallites size produced were large and in the range of photocatalytic crystallites size with an average of 17.2 nm to 28.9 nm. It phases composition also showed the best applicable composition with a mixture of 70% anatase and 30% rutile in addition with small thickness of 2.9µm as well as with small band gap of 2.85 eV which are good in enhancing photocatalytic activity. Further analysis with color degradation method confirmed that the fabricated TiO2 thin film of green sol gel with r = 5 showed the highest photodegraded of methylene blue of 97%± 0.5 under UV-light region and 86%± 1.8 under visible light region for five hours’ duration. As a conclusion, TiO 2 thin film of novel green sol gel route is successfully fabricated for better photocatalytic performance under both UV-light region and visible light region.